Structural and mechanical characterization of polyurethane-CaCO3 composites synthesized at high calcium carbonate loading: An experimental and theoretical study - de Moura, Ana P; da Silva, Enio HP; dos Santos, Vanessa S [UNESP]; Galera, Miguel F; Sales, Flaminio CP; Elizario, Sayonara [UNESP]; de Moura, Márcia R [UNESP]; Rigo, Vagner A; da Costa, Romeu RC (SAGE Publications, 2021)
Due to its exceptional biocompatibility, Polyurethane (PU) reinforced with calcium carbonate (CaCO3) is a composite material with significant biomedical applications. However, much of the currently known mechanical and chemical information regarding composites has been obtained at low and moderate CaCO3 content levels. This study employs experimental and theoretical tools to evaluate the structural, morphological, and mechanical properties of pristine polyurethane, and when doped with CaCO3 at 25 and 50 wt.%. In the experiments the samples are characterized using X-ray diffraction (XRD), infrared spectrophotometry (FT-IR), scanning electron microscopy (SEM), and tensile and flexural mechanical tests, while theoretical calculations are performed to evaluate the carbonate-polymer interaction. The XRD and FT-IR results indicate that CaCO3 is at the calcite phase and that PU-CaCO3 materials exhibit a broadening of bands related to the NH2 group. This result is explained using theoretical calculations that demonstrate a weak interaction between those molecules with the CaCO3 surface, where the molecule-calcite interaction occurs primarily through the NH2 molecular link. With respect to mechanical behaviour, the results show less fracture resistance and greater stiffness for the materials containing CaCO3, compared to those containing only PU. These results are explained in terms of the stress concentration due to CaCO3 within the polymer. Finally, the results detailed in this paper show that a high calcium carbonate loading is suitable for increasing the rigidity and decreasing the fracture toughness of the biomaterial, in association with a reduction of the plastic region.
Keywords: ab initio; calcite; calcium carbonate; composites; Polyurethane